Pengaruh Leverage dan Profitabilitas Terhadap Peringkat Obligasi Perusahaan Sektor Jasa Non Keuangan Terdaftar di BEI 2017-2020 - Gyzhella Chresty Angel; Lorina Siregar Sudjiman (Jurnal Ekonomis, 2021)
This study aims to determine how leverage, how profitability, and how leverage and profitability against bond rating service sector (non-financial) companies in Indonesia Stock Exchange 2017–2020 period. The population in this study is bond rating service sector (non-financial) companies listed in Indonesia Stock Exchange 2017-2020 period totaling 326 companies. The sampling technique used was purposive sampling in order to collect 28 samples service sector (non-financial) companies for 3 years of research. Data collection methods used in this study is a nonparticipant observation and the data required in this study is observational data obtained from www.idx.co.id. Based on the simultaneous test by logistic regression analysis with the help of SPSS 22 for windows, the result of this study shows that leverage (DER) does not have a significant effect to bond rating, profitability (ROA) have a significant positive effect towards bond rating, then leverage and profitability also have a significant positive effect on bond rating in service sector (non-financial) companies listed on Indonesia Stock Exchange 2017-2020 period.